Dissecting the BARMM Block Grant - Mendoza, Ronald U (Archīum Ateneo, 2019)
The Bangsamoro Autonomous Region in Muslim Mindanao (BARMM) was created under the Bangsamoro Organic Law (RA 11054 ) which was signed into law in March 2019. One key feature in this law is the creation of a BARMM block grant which is intended to help resource the new autonomous region which will replace the ARMM. In practical terms, setting up BARMM will hinge critically on the amount of financing it can mobilize — as well as the public finance management architecture which will serve as the governance system for BARMM’s finances. This brief article seeks to contribute to the discussions on operationalizing the block grant mechanism by briefly reviewing the international literature on the practice of block grant financing. It will also revisit the legislative discussions on the BOL — specifically on the block grant — in order to reveal some of the intended parameters underpinning this tool. Moving forward, both the national government agencies (notably the DBM) and their BARMM counterparts will need to tackle some key operational questions regarding the block grant. In lieu of answers at this stage, our note outlines some of these questions for immediate deliberation.